2007
DOI: 10.1108/13522750710754281
|View full text |Cite
|
Sign up to set email alerts
|

Just friends, good acquaintances or soul mates? An exploration of web site connectedness

Abstract: Purpose-This study aims to understand the meaning of web site connectedness from the consumer's point of view, and uncover the underlying meaning of emotional ties between visitors and web sites. Design/methodology/approach-The study, conducted a netnography which uses three qualitative research methods: online interviews; diary analysis; and observation of web site usage and behaviour. Seven respondents were obtained for the depth interviews, and 12 respondents participated in the diary study. The length of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Online content analysis of conversations (Venkatesh, Podoshen, Perri, & Urbaniak, 2014) in Jewish virtual communities was conducted in conjunction with the news analysis, which allowed the author to engage in a form of passive netnography (Maulana & Eckhardt, 2007), which is a naturalistic, unobtrusive method whereby online communities are examined. Netnographic analysis allows researchers to gain very valuable insight into the context of actual consumption conversations (Mkono, 2011).…”
Section: Methods and Datamentioning
confidence: 99%
“…Online content analysis of conversations (Venkatesh, Podoshen, Perri, & Urbaniak, 2014) in Jewish virtual communities was conducted in conjunction with the news analysis, which allowed the author to engage in a form of passive netnography (Maulana & Eckhardt, 2007), which is a naturalistic, unobtrusive method whereby online communities are examined. Netnographic analysis allows researchers to gain very valuable insight into the context of actual consumption conversations (Mkono, 2011).…”
Section: Methods and Datamentioning
confidence: 99%
“…To be able to have a more complete picture of this phenomenon and enrich academic knowledge, some studies have been done qualitatively [16]. Firstly, this study uses qualitative methods such as online interviews and netnography method explore the conceptualization of the web site attachment.…”
Section: Methodsmentioning
confidence: 99%
“…Childer et al [15] found that online retail shopping behavior can fulfill people's hedonic and utilitarian needs. Maulana and Eckhardt [16] introduced the web site connectedness which reflects the intensity of emotional ties and relational proximity between a visitor and a web site, and suggested the different type of relationships between a web site and its visitors are analogous to the relationships between two individuals or consumer and a brand. Therefore, the retail web sites may also become the material objects which people attached as the common products and brands.…”
Section: A Attachment Theory and Web Site Attachmentmentioning
confidence: 99%
“…Likewise, some of the researchers used other data collection techniques in addition to observation. Maulana and Eckhardt (2007) combined three data gathering techniques in cyber ethnographic research --online interviews, diary analysis and observation of the web site usage, and behavior in order to examine the web site connectedness. They interviewed seven respondents in depth and analyzed the data gathered from 12 respondents in the diary study.…”
Section: Ethnography and Cyber Ethnographic Researchmentioning
confidence: 99%